Circular RNA CCT3 is a unique molecular marker in bladder cancer - Lin Luo; Qingzhi Xie; Yunchou Wu; Ping Li; FuQiang Qin; Dunming Liao; KangNing Wang (BMC Cancer, 2023)
Abstract This study surveyed circular RNA CCT3 in bladder cancer (BCa). We recruited 85 BCa patients and 40 normal controls (Normal) and collected clinical specimens for analysis. circRNA CCT3 expression was analyzed by RT-qPCR, diagnostic accuracy was calculated by ROC curves, and survival outcomes were evaluated by survival curves. CircRNA CCT3 was overexpressed or knocked down in cells, thereafter to observe the changes in cell malignant phenotypes. The downstream molecules of circRNA CCT3 were detected. Our data suggest that circRNA CCT3 was upregulated in human BCa and was associated with poor survival outcomes of BCa patients. In cell experiments, overexpressing circRNA CCT3 promoted BCa cell malignancy, whereas silencing circRNA CCT3 did the opposite. In addition, circRNA CCT3 modulated PP2A expression by miR-135a-5p. This study demonstrates that circRNA CCT3 is a diagnostic and prognostic biomarker in BCa patients and is a tumor promoter in BCa.